The cordial man and his precursors: the European avant-garde - Rocha, João Cezar de Castro (Literatura e Sociedade, 2004)
In light of two hypotheses, the essay seeks to renew the understanding of Filippo Tommaso Marinetti's trip to South America in 1926. On the one hand, the performative character of the creator of futurism and the strictly commercial aspect of his conference tour are appreciated. On the other hand, Marinetti's behavior is contrasted with the practices that define the sociability of the "cordial man", as studied by Sérgio Buarque de Holanda in Raízes do Brasil.